2016
DOI: 10.1007/s11664-016-4971-x
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Properties of Boron Nitride-Ethylene Glycol (BN-EG) Nanofluids

Abstract: This paper presents the results of experimental investigation of the dielectric properties of ethylene glycol (EG) with various load of boron nitride (BN) nanoparticles. The nanofuids were prepared by using a two-step method on the basis of commercially available BN nanoparticles. The measurements were carried out using the Concept 80 System (NOVOCONTROL Technologies GmbH & Co. KG, Montabaur, Germany) in a frequency range from 10 Hz to 10 MHz and temperatures from 278.15 K to 328.15 K. The frequency-dependent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Meanwhile, BNNTS are basically electrically insulators and are appealing insulating materials with high thermal conductivity [35]. BN is also a highly stable dielectric ceramic material and interesting behaviour has been reported related to the electric and magnetic properties of nanofluids based on BN [36][37][38].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Meanwhile, BNNTS are basically electrically insulators and are appealing insulating materials with high thermal conductivity [35]. BN is also a highly stable dielectric ceramic material and interesting behaviour has been reported related to the electric and magnetic properties of nanofluids based on BN [36][37][38].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Jacek et al demonstrate that the addition of BN nanoplates in the ethylene glycol significantly increases the direct current (DC) and AC conductivity of base fluids. An 11‐fold increase in the dc conductivity is found for 20 wt.% of BN‐nanofluid [20]. Itseems that nanofluids with the same nanofillers but with different base fluid showed different dielectric performances.…”
Section: Introductionmentioning
confidence: 99%
“…Salehirad and Nikje 30 revealed that the addition of a low weight fraction of modified BN to the mineral oil could improve its thermal conductivity and electrical features without suppressing other properties. Fal et al 31 investigated the electrical conductivity of BN nanofluids. The results proved that the volume concentration could have an influence on electrical conductivity.…”
Section: Introductionmentioning
confidence: 99%